PENGARUH INVENTORY TURNOVER DEVIDEN PAYOUT RATIO DAN NET PROFIT MARGIN TERHADAP RETURN SAHAM PADA SEKTOR KESEHATAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018–2023 - Yogi Bernando Simamora; Waluyo Jati (Journal of Research and Publication Innovation, 2024)
This study aims to evaluate the impact of several financial variables on stock returns for healthcare companies listed on the Indonesia Stock Exchange (IDX) during the period from 2018 to 2023. The variables examined include Inventory Turnover (ITO), Dividend Payout Ratio (DPR), and Net Profit Margin (NPM). A quantitative method is used to analyze data from the financial reports of these companies. The results indicate that ITO, DPR, and NPM significantly affect stock returns, with a combined contribution of 30.8%. This suggests a relationship between inventory management efficiency, dividend policy, and profitability with the company's stock performance. However, the remaining 69.2% of stock returns are influenced by other factors not covered in this study. The study concludes that while ITO, DPR, and NPM significantly contribute to stock returns, other factors should also be considered to fully understand stock performance in the healthcare sector. These findings provide valuable insights for investors and company managers in making decisions related to investments and company policies.